OPPORTUNITIES AND CHALLENGES IN IMPLEMENTING INDEPENDENT LEARNING INDEPENDENT CAMPUS - Rahman, Fatur; Sukiman, Sukiman (Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2026)
The Merdeka Belajar–Kampus Merdeka (MBKM) policy represents a strategic initiative to transform higher education by enhancing the relevance of graduates to societal and professional demands. The Elementary Islamic School Teacher Education Program (PGMI) has distinctive characteristics that require contextualized implementation of MBKM aligned with the values ​​and practices of madrasah education. This article aims to analyze the opportunities and challenges of implementing MBKM in PGMI programs through a literature review. The research employed a non-PRISMA literature review method by examining relevant journal articles, conference proceedings, and policy documents published between 2015 and 2025. Data were collected through systematic literature searching and analyzed using content and thematic analysis techniques. The findings indicate that MBKM implementation in PGMI offers significant opportunities for strengthening pedagogical and professional competencies of prospective teachers, developing soft skills, promoting experiential and contextual learning, and expanding collaboration with madrasa partners. However, several major challenges were identified, including limited curriculum and lecturer readiness, issues related to credit recognition and conversion, constraints in madrasa partnerships, and the need to harmonize MBKM policies with the distinctive characteristics of Islamic education. The study concludes that the successful implementation of MBKM in PGMI programs depends on adaptive planning, institutional support, and the development of contextual MBKM implementation models that are responsive to the needs of madrasah-based teacher education.